The phylogenetic position of the enigmatic Atlantic forest-endemic spiny mouse Abrawayaomys (Rodentia: Sigmodontinae) - Ventura, Karen (2013)
Background The phylogenetic position of the sigmodontine genus Abrawayaomys, historically assigned to the tribe Thomasomyini or considered a sigmodontine incertae sedis, was assessed on the basis of nuclear and mitochondrial DNA sequences obtained from four individuals from different localities in the Atlantic forest of Brazil. Sequences of Abrawayaomys were analyzed in the context of broad taxonomic matrices by means of maximum-likelihood (ML) and Bayesian analyses (BA). Results The phylogenetic position of Abrawayaomys differed depending on the gene analyzed and the analysis performed (interphotoreceptor retinoid-binding protein (IRBP) ML: sister to Thomasomyini; IRBP BA: sister to Akodontini; cytochrome (Cyt) b ML: sister to Neotomys; and Cyt b BA: sister to Reithrodontini). With the sole exception of the BA based on Cyt b sequences, where the Abrawayaomys-Reithrodon clade had strong support, all sister-group relationships involving Abrawayaomys lacked any significant support. Conclusions As such, Abrawayaomys constitutes the only representative so far known of one of the main lineages of the sigmodontine radiation, differing from all other Atlantic forest sigmodontine rodents by having a unique combination of morphological character states. Therefore, in formal classifications, it should be regarded as a Sigmodontinae incertae sedis.